Hide-and-Seek with Tiny Neotenic Beetles in One of the Hottest Biodiversity Hotspots: Towards an Understanding of the Real Diversity of Jurasaidae (Coleoptera: Elateroidea) in the Brazilian Atlantic Forest - Biffi, Gabriel; Rosa, Simone Policena; Kundrata, Robin (Biology, 2021)
Jurasaidae are a family of neotenic elateroid beetles which was described recently from the Brazilian Atlantic Forest biodiversity hotspot based on three species in two genera. All life stages live in the soil, including the larviform females, and only adult males are able to fly. Here, we report the discovery of two new species, Jurasai miraculum sp. nov. and J. vanini sp. nov., and a new, morphologically remarkable population of J. digitusdei Rosa et al., 2020. Our discovery sheds further light on the diversity and biogeography of the group. Most species of Jurasaidae are known from the rainforest remnants of the Atlantic Forest, but here for the first time we report a jurasaid species from the relatively drier Atlantic Forest/Caatinga transitional zone. Considering our recent findings, minute body size and cryptic lifestyle of all jurasaids, together with potentially high numbers of yet undescribed species of this family from the Atlantic Forest and possibly also other surrounding ecoregions, we call for both field research in potentially suitable localities as well as for a detailed investigation of a massive amount of already collected but still unprocessed materials deposited in a number of Brazilian institutes, laboratories and collections.
Keywords: caatinga; systematics; Brazil; classification; distribution; paedomorphism; morphology; nature conservation